Damage characteristics and constitutive model of reconstituted weakly cemented mudstone subjected to water, pore, and constant-variable biaxial unequal confining pressure - Xiangqian Zhao; Jianbiao Bai; Yunbo Gou; Xiangyu Wang; Qingtao Liu; Yanhui Li; Dingchao Chen (Alexandria Engineering Journal, 2025)
Clarifying the bearing performance and damage mechanisms of reconstituted weakly cemented mudstone in engineering environments is significant for enhancing the stability of repaired weakly cemented mudstone roadways. Multidimensional research methods, including XRD, MIP, and water immersion experiments, were employed to reveal the influence of water content and porosity on the physical and mechanical properties of reconstituted weakly cemented mudstone. Based on the deformation and stress characteristics of the roadway roof, a constant-variable biaxial unequal confining pressure true triaxial numerical model was established. Results indicated that the strength of reconstituted weakly cemented mudstone increases with the increase in support strength, while it decreases in an exponential function form with increasing water content and porosity. Furthermore, a damage constitutive model for reconstituted weakly cemented mudstone under biaxial unequal confining pressure conditions was developed and revealing that the re-cemented body is the primary failure structure when reconstituted weakly cemented mudstone is loaded. Consequently, measures were proposed to modify reconstituted weakly cemented mudstone by injecting high water rapid-setting materials for filling, resulting in a significant increase in the strength of both the re-cemented body and the reconstituted weakly cemented mudstone after grouting. The findings of this study provide theoretical guidance for related engineering issues.